Syrjäkylä muutoksessa - Oksa, Jukka, 1945- (Joensuu : Joensuun yliopisto, 1998)
Abstract.
Tiivistelmä ja 10 erip.
Väitöskirja
Keywords: diskurssianalyysi; kylätutkimus; maaseutu; maaseutusosiologia; sosiaalinen muutos; syrjäseudut; diskursanalys; byundersökning; landsbygd; landsbygdssociologi; social förändring; perifera regioner; Eurooppa; Pohjois-Karjala.; Suomi; Europa; Norra Karelen; Finland; Euroopan unioni; väitöskirjat; doktorsavhandlingar